A Quick Guide to Speed-Dating Theorists through Thinking with Theory in Qualitative Research: Viewing Data Across Multiple Perspectives - Elsa Lenz Kothe; Marc Higgins; Sam Stiegler; Marie-France Berard; Brooke Madden (Canadian Society for Studies in Education, 2015)
Searching for a way to read, think, research, and write with complex theory, the authors of this book review came together for a peer-led doctoral reading group. Given our disparate disciplinary commitments, as well as our uncertainty as to how to embark on such a task, our group coalesced around the approach offered by Alecia Y. Jackson and Lisa A. Mazzei in Thinking with Theory in Qualitative Research: Viewing Data Across Multiple Perspectives. Jackson and Mazzei implicitly propose the format of speed-dating theorists within their book, which we found ideal for our theoretically promiscuous reading group. We offer a window into our speed-dating experiences through a creatively flirty medium: dating service profiles. Like the profiles, the productivity of using Thinking with Theory as a guide for promiscuous theoretical thinking, researching, and writing is not in its prescription but rather in the emergence of different productions of knowledge that occur relationally.